Modeling phaeopigment concentrations in water from a shallow mesotrophic lagoon. (29th October 2019) - Stoichev, Teodor; Duran, Robert; de Diego, Alberto; Vasconcelos, Vitor M.
Abstract: Concentrations of phaeopigments (Pha) and chlorophyll a (Chl) were determined in surface waters from a temperate lagoon during six sampling campaigns at high and at low tide. In order to develop models for phaeopigment concentration in water, it was necessary to replace Chl with photosynthetic pigment concentration ( P t = Pha+Chl) as one of the explanatory variables. Under first approximation, food availability and water temperature ( T ) could be considered as independent variables. The concentrations of Pha were then determined following seasonal change of response curves of the consumer community on T . However, multiple regression models with P t, T and, eventually, salinity as explanatory variables were better able to depict Pha. All equations, developed with P t, were also solved using Chl as an input variable. Although part of the performance was lost, such back‐transformed models can be used at low/medium T and moderate to high concentrations of Chl. The developed equations about middle to long‐term variations of Pha could be applied to study the biogeochemistry of contaminants related to Pha and to evaluate the dependence on temperature of phytoplankton utilization by consumers. Practitioner points: Phaeopigment concentration depicted by chlorophyll (Chl), temperature ( T ), and salinity. Better results obtained at low to medium T and moderate to high Chl concentration. Multiple regression (MR) better for extrapolation than model (S) with variable separation. Thermal response of consumer community in mesotrophic lagoon studied using model S. Abstract : Developed models for phaeopigments (Pha) concentration in lagoon waters as function of chlorophyll a (Chl) concentration, water temperature ( T ) and salinity (Sal). The most important variables were T and Chl. Two types of models were compared: multiple regression analysis or with separation of variables.